Mangrove crab uses victory display to "browbeat" losers from re‐initiating a new fight. (12th October 2017) - Chen, Paul Z.; Carrasco, Roman L.; Ng, Peter K. L.
Abstract: Signalling behaviour is integral to animal contests. However, post‐contest signals, such as victory displays, have received relatively little attention. One hypothesised function of victory displays is to ensure a more lasting dominance by reducing the risk of losers re‐initiating a new contest with winners. Despite several theoretical studies using game theory that support this hypothesis, empirical support for the understanding of when and why victory displays are used with respect to browbeating is lacking. We use a common South‐East Asian mangrove crab, Perisesarma eumolpe, to examine whether the performance of victory displays by winners, among other factors, affects the time of fight re‐initiation by losers, if at all re‐initiated. Using mixed‐effects survival analysis models, we analysed 77 fights from 27 staged contest trials between randomly paired males. We found losers that experienced victory display performed by winners, presented a decreased instantaneous hazard rate of re‐initiating a new fight than losers that did not. These results corroborate previous game theoretical models indicating that victory displays may function to reduce the chances of losers re‐initiating another fight. In discouraging losers from restarting a fight, winners reduce the potential costs of a future contest.